Application Of Surgical Safety Checklist (WHO) at Al-Yarmouk Teaching hospital - Obyeis, Akeel Lateef; Ahmed A,; Shakir, Rafid Monneir (International Journal of Psychosocial Rehabilitation, 2020)
Surgery-related complications are quite common and often avoidable. We aimed to verify the usefulness of a 19-item Surgical Safety Checklist, based on WHO guidelines, to reduce the rate of complications and deaths associated with non-cardiac surgery.Over a one-year period, a total of 162 patients scheduled for various non-cardiac surgical operations were included in the study. Patients were followed up for up to 30 days after surgical intervention.Using the 19-item surgical safety checklist, the risk of surgical site infection (SSI), respiratory complications, missed gauze, and blood loss requiring transfusion were comparable to UIC results of the World Health Organization (3.7%, 2.4%, 0.69 and 1.85%, respectively). Pulse oximeter was used in 92.5% and site marking in 65.4%. Antibiotic prophylaxis was used in 61.7% of patients in which just 3.7% developed SSI, while the extended regimen used in 38.3% of patients resulted in SSI rate of 9.8%. No mortality was reported during the period of the study.The Surgical Safety Checklist is a simple cheap and effective method to reduce surgical complications in daily clinical practice. We recommend the use of the Surgical Checklist in all operations with modifications made for different surgical specialties.